As representações populacionais de Richard Francis Burton: Uma análise do processo de constituição do discurso sobre populações não Européias no Século XIX - Gebara, Alexsander Lemos de Almeida (Revista de História, 2003)
This text intend to understand the transformations on the populational descriptions of Richard Burton between 1849 and 1869. The central hypothesis is that a more effective comprehension of those representations is possible when one analyses several issues like the motivations and the experience of the travel and the locus of authority of the writer